Expression of discoidin domain receptors in 3T3-L1 preadipocytes and adipocytes - Zurakowski, Honorata (University of Ottawa (Canada), 2006)
Discoidin domain receptors (DDRs) are receptor tyrosine kinases, of which there are members, DDR1 and DDR2, which are activated by collagen and are involved in cellular proliferation. Therefore, given their role in extracellular matrix interactions and proliferation, both of which affect adipogenesis, we hypothesized that the DDRs influence preadipocyte biology, adipogenesis and adipocyte biology. DDR1 protein expression was decreased in 3T3-L1 a dipocytes versus preadipocytes, whereas, DDR1 mRNA expression was decreased at day 4 of 3T3-L1 adipogenesis compared to day 0. DDR2 mRNA expression was reduced at day 2 compared to day 0 of adipogenesis. DDR2-overexpressing preadipocytes display reduced subconfluent 3T3-L1 proliferation and reduced mitotic clonal expansion. DDR2-overexpressing adipocytes were larger and had a greater triacylglycerol mass compared to empty-vector control adipocytes. DDR2-overexpressing adipocytes exhibited a decrease in insulin-stimulated phophorylation of IRS-1 and an increase in Akt and ERK1/2 phosphorylation. Overexpression of DDR2 in preadipocytes also led to decreased phophorylation of IRS-1 upon stimulation with insulin, without an effect on Akt and ERK1/2 phosphorylation. These results suggest that DDR2 is pertinent to 3T3-L1 adipogenesis.
Keywords: Biology, Cell.